2011
DOI: 10.1007/s00784-011-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of inclinations of the mandibular fossa by computed tomography in an Asian population

Abstract: This study aims to evaluate the inclinations of right and left sides the mandibular fossa in Asian population using computed tomography (CT) images and determine its effects according to the parameters of gender, age, and asymmetry. CT images of the heads of 198 Asian subjects [95 females aged 44.2 ± 20.7 years, range 11-88 years; and 103 males aged 44.5 ± 19.7 years, range 15-98 years] were selected. The following eight parameters characterizing the inclinations of the mandibular fossa were measured by medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 17 publications
3
29
1
Order By: Relevance
“…Our results agree with those reported by Wu et al, 3 who found a moderate correlation between age and AE angulation in males, and also observed a positive correlation in women. Conversely, there was no positive correlation in our study between female angles and age, which can be explained by the differences in the populations studied: Wu et al 3 evaluated 95 exams of Asian female patients (aged 11 and 88 years), whereas we analyzed 184 exams of Brazilian female patients (aged 20 to 82 years). Hence, we examined a larger sample of different ethnicity and did not include ages younger than 20 years, since the joints are not fully formed before then.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results agree with those reported by Wu et al, 3 who found a moderate correlation between age and AE angulation in males, and also observed a positive correlation in women. Conversely, there was no positive correlation in our study between female angles and age, which can be explained by the differences in the populations studied: Wu et al 3 evaluated 95 exams of Asian female patients (aged 11 and 88 years), whereas we analyzed 184 exams of Brazilian female patients (aged 20 to 82 years). Hence, we examined a larger sample of different ethnicity and did not include ages younger than 20 years, since the joints are not fully formed before then.…”
Section: Discussionsupporting
confidence: 93%
“…Comparing the right and left sides of the TMJ, there were no differences in the mean angulation of the AEs, which is similar to that found by Csadó et al 4 In addition, the comparison between the right and left sides in females and males also showed no statistical differences between the means of the angles, as corroborated by Wu et al 3 A tendency for the AE angle to increase above the age of 30 years was observed in males. Our results agree with those reported by Wu et al, 3 who found a moderate correlation between age and AE angulation in males, and also observed a positive correlation in women.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…1) Past studies reported that 41% of the population have signs related to temporomandibular disorders (TMD) such as myofascial pain, TMJ internal derangement and TMJ degeneration. 2) One of the signs of TMD is TMJ osteoarthritis (TMJ OA), 1) which causes tissue degeneration due to the imbalance between the mechanical and biological synthesis and degradation of articular cartilage chondrocytes, extracellular matrix and subchondral bone.…”
Section: Introductionmentioning
confidence: 99%
“…Th e morphology of the articular eminence, glenoid fossa and mandibular condyle depends on numerous factors, such as changes in dentition associated with aging (tooth loss, attrition and/or increased function), degenerative changes of the glenoid fossa, masticatory stress, craniofacial growth, gender, ethnicity and the relationship between the fossa and the eminence in relation to the facial structures 4,6,[10][11][12][13] . Its functional morphology also depends on the morphological changes of the cranial base during ontogeny and hominid evolution, and mechanical properties of the craniofacial skeleton (environmental factors, food consistency and toughness) 4 .…”
Section: Introductionmentioning
confidence: 99%